Review of LCA studies of solid waste management systems – Part I: Lessons learned and perspectives - Laurent, Alexis; Bakas, Ioannis; Clavreul, Julie; Bernstad, Anna; Niero, Monia; Gentil, Emmanuel; Hauschild, Michael Z.; Christensen, Thomas H. (Waste management (Elmsford), 2014)
•We perform a critical review of 222 LCA studies of solid waste management systems.•Studies mainly concentrated in Europe with little application in developing countries.•Assessments of relevant waste types apart from household waste have been overlooked.•Local specificities of systems prevent a meaningful generalisation of the LCA results.•LCA should support recommendations representative of the local conditions. The continuously increasing solid waste generation worldwide calls for management strategies that integrate concerns for environmental sustainability. By quantifying environmental impacts of systems, life cycle assessment (LCA) is a tool, which can contribute to answer that call. But how, where and to which extent has it been applied to solid waste management systems (SWMSs) until now, and which lessons can be learnt from the findings of these LCA applications? To address these questions, we performed a critical review of 222 published LCA studies of SWMS. We first analysed the geographic distribution and found that the published studies have primarily been concentrated in Europe with little application in developing countries. In terms of technological coverage, they have largely overlooked application of LCA to waste prevention activities and to relevant waste types apart from household waste, e.g. construction and demolition waste. Waste management practitioners are thus encouraged to abridge these gaps in future applications of LCA. In addition to this contextual analysis, we also evaluated the findings of selected studies of good quality and found that there is little agreement in the conclusions among them. The strong dependence of each SWMS on local conditions, such as waste composition or energy system, prevents a meaningful generalisation of the LCA results as we find it in the waste hierarchy. We therefore recommend stakeholders in solid waste management to regard LCA as a tool, which, by its ability of capturing the local specific conditions in the modelling of environmental impacts and benefits of a SWMS, allows identifying critical problems and proposing improvement options adapted to the local specificities.